Distance Education and the Open University of Brazil: History, Structure, and Challenges - Baxto da Silva, Welinton; Amaro, Rosana; Mattar, João (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Correspondence courses have been offered in Brazil since the late 19th century; in the 20th century, instructional media such as radio and television were successfully used long before the introduction of the Internet. However, distance education (DE) was officially established in Brazil only in 1996 by the National Educational Law of Policies and Bases. Several censuses conducted by the Brazilian Ministry of Education and the Brazilian Association of Distance Education (ABED) collected statistics on the number of institutions and students involved in DE in Brazil. Although higher education DE has developed in the country since then, several attempts to create an Open University failed. The institution that is now The Open University of Brazil (UAB), created in 2005, focused mainly on teacher education. However, it is not a new institution (but rather a system of older institutions). It is neither a university (but rather a consortium of public federal, state, and municipal face-to-face educational institutions), nor open (candidates should have at least finished high school and are required to pass a rigorous entrance exam). Although UAB certainly contributed to the progress of DE in Brazil, it faces many challenges and problems, such as the continuously questioned quality of its learning support centers, labor relations, issues related to hiring face-to-face and online tutors, and the structure and organization of producing content for courses. This article presents a brief history and the main characteristics of DE in Brazil, details UAB’s structure, and discusses the challenges it faces.